2011
DOI: 10.1002/ajmg.a.33975
|View full text |Cite
|
Sign up to set email alerts
|

The Richieri‐Costa and Pereira syndrome: Report of two Brazilian siblings and review of literature

Abstract: Richieri-Costa and Pereira syndrome is a rare autosomal recessive disorder characterized specially by Pierre Robin sequence with cleft mandible and limb anomalies. There are a typical laryngeal anomaly which encompass short and round larynx, absent or abnormal epiglottis, and abnormal aryepiglottic folds. Most patients reported were from Brazil. We describe a brother and sister with Richieri-Costa and Pereira syndrome on another Brazilian family documenting their physical findings and laryngeal defects. We als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…History showed consanguinity and recurrence in sibs and a higher mortality rate in males, suggesting autosomal recessive inheritance of this condition. To the present, 32 Brazilian cases have been described [Richieri‐Costa and Pereira, ; Tabith and Bento‐Goncalves, ; Golbert et al, ; Graziadio et al, ; Favaro et al, ; Ogando et al, ; Souza et al, ; Tabith and Bento‐Goncalves, 1996; Guion‐Almeida and Richieri‐Costa, ], and one non‐Brazilian case [Walter‐Nicolet et al, ]. The possibility of a common ancestry of these patients was raised [Favaro et al, ], and the possibility of allelic heterogeneity [Ferreira de Lima et al, ], Recently, a 16–20 nucleotides repeat at the 5′ UTR of the EIF4AE gene was identified as the mutation leading to RCPS [Favaro et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…History showed consanguinity and recurrence in sibs and a higher mortality rate in males, suggesting autosomal recessive inheritance of this condition. To the present, 32 Brazilian cases have been described [Richieri‐Costa and Pereira, ; Tabith and Bento‐Goncalves, ; Golbert et al, ; Graziadio et al, ; Favaro et al, ; Ogando et al, ; Souza et al, ; Tabith and Bento‐Goncalves, 1996; Guion‐Almeida and Richieri‐Costa, ], and one non‐Brazilian case [Walter‐Nicolet et al, ]. The possibility of a common ancestry of these patients was raised [Favaro et al, ], and the possibility of allelic heterogeneity [Ferreira de Lima et al, ], Recently, a 16–20 nucleotides repeat at the 5′ UTR of the EIF4AE gene was identified as the mutation leading to RCPS [Favaro et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective review of the clinical characteristics from 35 individuals reported in detail in the literature, previously to the uncovering of the molecular mechanism responsible for RCPS, was performed. [3][4][5][8][9][10][11][12][13][14][15][16][17] The main clinical findings obtained in this review were compared to those found in the cohort of this study. In the comparison between the 2 groups, Fisher's exact test, 2-tailed, was applied along with Bonferroni correction for 26 tests.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[15,16,17,18]. Accordingly, alterations in genes that are known to play diverse roles during carcinogenesis, such as CDH1, TP63, NBS and AXIN2, have been related to both syndromic and non-syndromic cleft lip/palate [19,20,21,22,23,24]. Moreover, both are common diseases with significant genetic heterogeneity; therefore, an aetiological overlap is more likely to occur when compared to other diseases.…”
Section: Non-syndromic Cleft Lip With or Without Cleft Palate (Nscl/pmentioning
confidence: 99%
“…Sequencing of EIF4A3 in five additional Brazilian affected individuals ascertained elsewhere 23,24 revealed that four of them (individuals 21 to 24, including 2 siblings) were homozygous for the 16-repeat allele. In contrast, the fifth (individual 25) was a compound heterozygote, possessing a 14-repeat allele in trans with a nucleotide change, c.809A>G (EIF4A3 transcript, NM_014740.3), which leads to an amino acid substitution at Asp270 (p.Asp270Gly) (Figure 3).…”
Section: Cdh1 Promoter Methylation In Familial Ns Cl/pmentioning
confidence: 99%
See 1 more Smart Citation